Modelling of mechanical roots on slope stability - Yulia Amirul Fata; Hendrayanto Hendrayanto; Erizal Erizal; Suria Darma Tarigan; Takeshi Katsumi (Journal of Degraded and Mining Lands Management, 2023)
Root system mechanical reinforcement through root-soil cohesion on slope stability is important. However, the root cohesion of Tectona grandis, Maesopsis eminii, and shrubs (Chromolaena odorata) on slope stability is rarely studied and modelled. This study aimed to model the mechanical effect of vegetation through root cohesion, namely teak (Tectona grandis), Maesopsis eminii, and shrubs (Chromolaena odorata). The study was conducted in a simultaneous landslide on January 1, 2020, that dominantly occurred on vegetated slopes of Sukajaya District, Bogor Regency, West Java. The Wu model's root cohesion (CR) was modelled on slope stability using a modified Bishop model. The modelling used the data from field and laboratory-measured. The study found that the presence of a root system increases slope stability's factor of safety (FOS). The root system of young Maesopsiss eminii produces the largest effect of FOS compared to the root system of shrubs, teak, and old Maesopsis eminii. The slope stability of vegetated slopes is a function of the CR and the effective root zone depth. The highest total CR of vegetation was teak with 0.398 kPa, followed by shrubs, young Maesopsis eminii, and old Maesopsis eminii with 0.202 kPa, 0.191 kPa, and 0.087 kPa, respectively. The effective root zone of teak, young Maesopsis eminii, and shrub were 500, 230, 140, and 66 cm, respectively.